Accounting Approach to Corporate Social Responsibility - T. Yu. Serebryakova (Учёт. Анализ. Аудит, 2023)
The worldwide recognized the idea of the need to inform the public about the measures taken by the company in environmental conservation and social activities. The business community is increasingly involved in the activity of presenting non-financial reporting. However, it rarely inspires confidence in a reasonable user because of the generalization’s opacity and the arbitrary principle of presentation. At the same time, one of them is the least researched — reporting on corporate social responsibility (CSR). The study’s goal is to consider the accounting possibility and evaluating CSR for non-financial types of reporting of organizations in the reliability’s context of the information disclosed, public needs, methods of formation and stakeholders. The work used general scientific methods of cognition: a systematic approach, logical generalization, linguistic analysis and hypotheses. The author showed it was CSR reporting that had exposed to a significant risk of manipulation, containing a variety of incomparable information that depended on the industry, nature of business, regulatory restrictions, market position and other circumstances. Many recognize the need for participation in preparing such reporting accounting technology. The accounting community is not optimistic about the attempt by the IASB to create standards for non-financial reporting using financial instruments that just investors are interested in. If stakeholders have a genuine interest in disclosing non-financial information in reporting, it is necessary to create really proper accounting systems. That would allow for generalizing the data about CSR. The main conclusion is directed to the existing need for the state policy development in this area and public administration systematically.